Minat Siswa Dalam Pembelajaran Sepak Bola (Bola Atom) Pada Siswa Kelas 6 MI Kanzul Huda (Fullday School) Tahun Pelajaran 2025-2026 - Bayu Nugraha Murdiansyah (CV. Multi Kreasi Media, 2026)
From the results of preliminary study conducted by researchers at mi kanzul huda, that not all students of mi kanzul huda are active in following their football learning tend to be lazy, there are less serious in following physical education lessons mainly football subjects.The reason for this is the lack of interest of students, because of a less qualified learning process, less clear task tasks as well as less firm instructions so that students are less enthusiastic in following football learning. The study aimed to identify student interest in learning football.The research is research survey used the descriptive qualitative research.The research sample areas students 6 mi kanzul huda covering 25 students.Data collection techniques use instruments in the form of interest research student learning, already tested validity and reliability.Analysis techniques qualitative data using descriptive statistics.As for checking the validity of data using validity and reliability of data cross check as a method of triangulation. Through data analysis can be seen on very high as many as 24 0 % and high as many as 32 % % while criteria are, low 40 % % and very low 4, this is viewed from two factors namely internal and external indicators of in some of them, favorite, interest, attention, curiosity, while the outside of the role of teachers and facilities.The highest category survey students show lower with the percentage of 40 %. Based on the analysis of the data can disimplukan that research can be used as reference or benchmark especially physical education teachers, sport and health especially in teaching material football.